2018
DOI: 10.1002/cta.2557
|View full text |Cite
|
Sign up to set email alerts
|

Design trade‐offs of a capacitance‐to‐voltage converter with a zoom‐in technique for grounded capacitive sensors

Abstract: This paper presents a low-power, high-precision capacitance-to-voltage converter (CVC) for grounded capacitive sensors. To measure very small capacitance variations in the presence of a large offset capacitance, a new zoom-in structure is proposed. The major non-idealities of the CVC such as the settling error, charge injection, and parasitic capacitance of the switches are minimized through an optimized design. Accordingly, it is shown that the zoom-in technique can significantly reduce many of these errors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In the following section, the major nonidealities of the designed interface will be described. It will be shown that the zoom‐in CVC with autocalibration can reduce more efficiently the effect of any nonidealities affecting the performance of the interface, compared with the conventional CVC and the zoom‐in CVC in Ahmadpour Bijargah et al Because of the essential role of the CVC, first the operation principle of the CVC with zoom‐in structure is introduced in Section . The rest of the interface is elaborated in Section .…”
Section: Capacitance Measurement Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…In the following section, the major nonidealities of the designed interface will be described. It will be shown that the zoom‐in CVC with autocalibration can reduce more efficiently the effect of any nonidealities affecting the performance of the interface, compared with the conventional CVC and the zoom‐in CVC in Ahmadpour Bijargah et al Because of the essential role of the CVC, first the operation principle of the CVC with zoom‐in structure is introduced in Section . The rest of the interface is elaborated in Section .…”
Section: Capacitance Measurement Systemmentioning
confidence: 99%
“…Figure A shows the zoom‐in CVC structure for a grounded capacitive sensor . A conventional CVC is also shown within the dashed rectangle.…”
Section: Capacitance Measurement Systemmentioning
confidence: 99%
See 3 more Smart Citations